Higher blood pressure among Inuit migrants in Denmark than among the Inuit in Greenland. Issue 4 (1st April 2002) - Bjerregaard, P; Jørgensen, M E; Lumholt, P; Mosgaard, L; Borch-Johnsen, K
Abstract : Study objective: Previous studies of blood pressure among the Inuit have given inconsistent results and studies comparing Inuit migrants with those living in traditional Inuit areas are absent. The purpose of the study was to compare the blood pressure of the Inuit in Greenland with that of Inuit migrants in Denmark. Design: Questionnaire, interview, and clinical examination in a cross sectional random population sample. Setting: A population based survey among Inuit in Greenland and Inuit migrants in Denmark. Participants: 2046 Inuit aged ≥18, 61% of the sample. Main results: Age and gender adjusted blood pressures were 117/72 mm Hg in Greenland and 127/81 mm Hg among the migrants (p<0.001). In both populations, blood pressure increased with age and body mass index, and was higher among men and non-smokers. In Greenland, blood pressure increased with the level of school education. The associations with Inuit heritage, alcohol, diet, and physical activity were not significant. The difference between the two populations persisted after adjusting for age, gender, body mass index, education, and smoking. Among those who had completed high school, there was no difference between the systolic blood pressure of the two populations while the difference for diastolic blood pressure was much less than for those with less education. Conclusions: Blood pressure was lower among the Inuit in Greenland than among the Inuit migrants in Denmark but the difference was absent (systolic pressure) or reduced (diastolic pressure) among the better educated. The results suggest that the blood pressure of the Inuit, especially Inuit men, may be responsive to factors related to the modern Western way of life.